Development and Evaluation of An In-House Lumbar Puncture Simulator for First-Year Resident Lumbar Puncture Procedure Learning - Muñoz Leija, David; Díaz González Colmenero, Fernando; Ramiréz Mendoza, Diego A; López Cabrera, Norma Guadalupe; Llanes Garza, Hilda Alicia; Palacios Ríos, Dionicio; Negreros Osuna, Adrian Antonio (2024)
Introduction: Lumbar puncture (LP) is a common invasive technique considered an essential learning milestone for anesthesiologists due to its application in spinal anesthesia. We aimed to develop an in-house LP simulator, test its effectiveness in learning the steps to perform an LP and analyze its impact on the firstyear residents' self-confidence at our hospital. Methods: We used 3D printing and silicone casting to create an LP simulator based on a lumbar spine computed tomography (CT). We divided 12 first-year anesthesiology residents into control and experimental groups. The control group received traditional training, while the experimental group practiced with the simulator for three months. We used a procedure checklist and a Likert scale survey to evaluate their procedural knowledge and self-confidence at baseline, three, and six months. Eighteen months later, we evaluated their LP performance skills. Results: Both groups showed a significant improvement in their knowledge scores over time. After three months, the experimental group had a higher median knowledge score (10 (10 - 10) median (min-max)) than the control group (9 (8 - 9.5) median (min-max)) (p = 0.03). While there were no apparent differences in median self-confidence scores between the groups at any time point, the experimental group had a significant increase in their self-confidence for performing an unassisted LP, with a median score of 1/5 (1 2.3) at baseline and 5/5 (4.8 - 5) after six months (p = 0.006). In contrast, the control group's self-confidence scores decreased from 4/5 (3 - 4) after three months to 3/5 (2 - 5) after six months. The evaluation of performance skills did not yield statistically significant results. Conclusion: Our study demonstrates that an in-house LP simulator is an effective and practical approach for first-year anesthesiology residents to learn the LP procedure. This approach could be particularly useful in settings with limited resources and a lack of sufficient patients to practice on, as it provides an opportunity for faster learning and increased self-confidence.